Making a Good Death: AIDS and Social Belonging in an Independent Church in Gaborone - Klaits, Frederick (Botswana Notes & Records, 1998)
This article discusses the material and moral dimensions of the current AIDS crisis as experienced by members of a small independent church in Gaborone, Botswana. A case study, based on participant-observation research, is presented of a young woman church member whose illness and death provoked those involved in her care to reflect upon and debate the nature of her social loyalties. The article explores the multiple social and emotional significances of caretaking, of death, and of the religious and medical languages in which suffering is discussed. It is suggested that there is a need for AIDS prevention programs in Botswana to find ways to build on popular ways of affirming social belonging in the context of suffering.
Free